COMMUNICATION STRATEGY OF THE ISLAMIC HIGHER EDUCATION INSTITUTION IN JEMBER IN COUNTERING RADICALISM - Ach Wahidi (Indonesian Journal of Islamic Communication, 2022)
Radicalism often becomes a terrifying and unsettling threat to society due to its religious ideology that is no longer contextual. Religious study circles (*halaqoh*) are conducted by preachers and lecturers who hold extreme views and apply rigid normative religious laws (texts) to current social and political conditions. In spreading radical doctrines, university students are typically the primary targets, as they are considered capable of carrying out the mission. This journal focuses on two main issues: the communication strategies employed by IAIN Jember’s campus organization to counter radicalism, and the role of organizational communication in this effort. The methodology of this study is qualitative descriptive, based on both literature review and field research. It aims to understand the conditions or phenomena experienced by the subjects and describes them using scientific language. The research findings show that IAIN Jember has taken significant and serious steps to combat radicalism, such as organizing seminars with themes related to the dangers of radical ideologies. These initiatives represent the campus's proactive communication strategy to foster awareness and resilience among students.